A kind of ultra-high temperature resistant elastic wall flat cable
By designing flat cables with flat structures with ultra-high temperature elastic walls, using high-efficiency insulation materials such as illiite-based aerogel felt and mica belt wrapping, the problems of short power-on time and large space occupancy in existing cables in ultra-high temperature environments are solved, and long-term power-on and space efficiency optimization in ultra-high temperature environments are achieved.
Patent Information
- Application Number
- CN202411691041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
It is difficult for existing cables to maintain normal power in ultra-high temperature flame environments, and the space occupies a large amount of space, making it difficult to effectively lay out in environments such as missiles with limited space.
The ultra-high temperature-resistant elastic wall flat cable adopts a flat structure. The cable core consists of conductors, polyimide film insulation layer, mica belt wrapping layer, illite-based aerogel felt and aramid fiber sleeve. It forms an efficient insulation and protective layer by braiding inorganic fibers such as quartz fiber and glass fiber.
Under an ultra-high temperature flame of around 2000°C, the cable can be powered normally for more than 120 minutes, and it occupies a small area. It is suitable for layout in an environment with limited space and is more convenient to install and maintain.
Smart Images

Figure CN119170331B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, in particular to an ultra-high temperature resistant elastic-wall flat cable. Background Art
[0002] Cables are the "blood vessels" and "nerves" of mechanical equipment, transmitting electrical energy and information that maintain its normal operation. For missile-shaped aircraft, the limited internal space and the ultra-high temperatures of around 2000°C generated by the instantaneous exhaust plume during launch place even higher demands on cable design. Summary of the Invention
[0003] Purpose of the invention: In order to solve the above technical problems, the present invention proposes an ultra-high temperature resistant elastic wall flat cable.
[0004] The technical solutions adopted are as follows:
[0005] An ultra-high temperature resistant elastic wall flat cable: having a flat structure, woven with a cable core as the braiding yarn and inorganic fiber as the axis yarn;
[0006] The cable core comprises, from the inside to the outside, a conductor, a polyimide film insulation layer, a first mica tape wrapping layer, an illite-based aerogel felt, a second mica tape wrapping layer and an aramid fiber sleeve;
[0007] The ultra-high temperature resistant elastic wall flat cable can be continuously powered normally for more than 120 minutes at a flame temperature of 1950-2050°C.
[0008] Furthermore, the preparation method of the illite-based aerogel felt is as follows:
[0009] After the illite is crushed, it is thoroughly washed with deionized water and dried. After calcination, it is added to a sodium hydroxide solution. After a sealed hydrothermal reaction at 120°C for 10 hours, the precipitate is filtered out, the filtrate is collected and its pH is adjusted to 6, and the fiber felt is added thereto and fully soaked to obtain a wet fiber felt. The wet fiber felt is then aged, solvent replaced, and then dried.
[0010] Furthermore, the calcination temperature is 400-600° C., and the calcination time is 1-5 hours.
[0011] Furthermore, the concentration of the sodium hydroxide solution is 2-6 mol / L.
[0012] Furthermore, the aging temperature is ≥60° C., and the aging time is 1-5 hours.
[0013] Furthermore, the aging is carried out in an ionic liquid.
[0014] Furthermore, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate and / or 1-butyl-3-methylimidazolium tetrafluoroborate.
[0015] Furthermore, during the solvent replacement, the reaction mixture was replaced in deionized water, ethanol and n-hexane for 1-3 days respectively.
[0016] Furthermore, the drying temperature is ≤50°C.
[0017] Furthermore, the inorganic fibers are quartz fibers and / or glass fibers.
[0018] Beneficial effects of the present invention:
[0019] The present invention provides an ultra-high temperature resistant, bullet-walled flat cable. Its unique flat structure enables it to be neatly arranged and occupies less space. When space is limited inside a missile, this allows for more efficient use of space, reduces the area occupied by the cable, and optimizes the layout. Furthermore, the cable is more convenient to install and maintain, can more easily pass through narrow spaces and complex wiring paths, and is easier to troubleshoot and replace during maintenance. Furthermore, the cable can withstand instantaneous ultra-high temperature flames and can continue to operate normally for more than 120 minutes under ultra-high temperature flames of approximately 2000°C.
[0020] The polyimide film in the cable of the present invention has an operating temperature of -65 to 260°C, and can reach 500°C in a short period of time. It has excellent electrical properties and weather resistance, and can prevent short circuit breakdown when the cable is subjected to high-temperature flame spray.
[0021] Mica tape has excellent high-temperature resistance, with a melting point as high as 1375°C and no water of crystallization. Therefore, it has a large safety margin at high temperatures and can withstand high temperatures for long periods of time while maintaining stable performance. In the present invention, the first mica tape wrapping layer, the second mica tape wrapping layer, and the illite-based aerogel felt form a "sandwich" type insulation interlayer, which can effectively maintain the stable operation of the cable in ultra-high temperature environments.
[0022] Illite is a common crystalline mineral that can be activated by calcination, causing the tetrahedral and octahedral structures in its structure to adjust and deform, thereby changing the chemical environment of aluminum and silicon and enhancing the dissolution reaction activity in sodium hydroxide solution. In addition, Al-Si-O composite oxides may be generated during the hydrothermal reaction, gelation and aging processes, providing stronger support for the aerogel skeleton and preventing pore collapse, thereby achieving better thermal insulation. Aging conditions have a significant impact on the microstructure of the aerogel. The present invention uses ionic liquid as an aging solvent, which can avoid damage to the gel skeleton and effectively promote dehydration condensation between gel particles, thereby enhancing the dissolution and reprecipitation of the aerogel skeleton particles. Under the unique induction effect of the ionic liquid, more nano-microporous structures are formed, the pore volume is increased, and the thermal insulation effect is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of the cable core in Example 1, where the numbers represent:
[0024] 1001-conductor, 1002-polyimide film insulation layer, 1003-first mica tape wrapping layer, 1004-illite-based aerogel felt, 1005-second mica tape wrapping layer, 1006-aramid fiber sleeve;
[0025] Figure 2 This is a schematic diagram of the structure of the ultra-high temperature resistant elastic wall flat cable in Example 1, where the reference numerals represent:
[0026] 1-cable core, 2-quartz fiber. DETAILED DESCRIPTION
[0027] Unless otherwise specified, the following examples and comparative examples were conducted in parallel, using the same processing steps and parameters.
[0028] Example 1:
[0029] An ultra-high temperature resistant elastic wall flat cable, with a cable core 1 as the braiding yarn and a quartz fiber 2 as the axis yarn, is woven into a flat structure on a KBL type braiding machine. The specific structural diagram is shown in FIG. Figure 2 As shown;
[0030] The cable core 1 includes, from the inside to the outside, a conductor 1001, a polyimide film insulation layer 1002, a first mica tape wrapping layer 1003, an illite-based aerogel felt 1004, a second mica tape wrapping layer 1005, and an aramid fiber sleeve 1006.
[0031] The preparation method of illite-based aerogel felt 1004 is as follows:
[0032] Take 1000g of illite, crush it through an 80-mesh sieve, wash it thoroughly with deionized water, remove water-soluble impurities, and then dry it in an 80℃ oven for 24h. Take it out and place it in a 500℃ muffle furnace for calcination for 2h to obtain activated illite powder. Add the activated illite powder to 10L of 4mol / L sodium hydroxide solution, stir it thoroughly and mix it evenly, seal it and heat it to 120℃ for hydrothermal reaction for 10h. After returning to room temperature, filter it, collect the filtrate and adjust its pH with 1mol / L hydrochloric acid solution To 6, add glass fiber felt and immerse it for 60 minutes, take it out and let it stand until no slurry drips to obtain wet fiber felt, then immerse the wet fiber felt in an appropriate amount of 1-butyl-3-methylimidazolium hexafluorophosphate and heat it to 70°C. After heat aging for 2 hours, take it out and let it stand until no liquid drips, then place it in deionized water for replacement for 2 days, and then place it in ethanol and n-hexane respectively for replacement for 1 day. During the replacement, replace the fresh solvent every 12 hours, and finally dry it in a 50°C oven for 24 hours.
[0033] The fire resistance performance of the ultra-high temperature resistant elastic wall flat cable prepared in this embodiment was tested with reference to Appendix D fire resistance test in the British fire-resistant cable standard BS6387. The test flame temperature was 2000±50°C and the continuous normal power-on time was ≥120min.
[0034] Example 2:
[0035] The process is basically the same as Example 1, except that 1-butyl-3-methylimidazolium tetrafluoroborate is used instead of 1-butyl-3-methylimidazolium hexafluorophosphate.
[0036] The preparation method of illite-based aerogel felt 1004 is as follows:
[0037] Take 1000g of illite, crush it through an 80-mesh sieve, wash it thoroughly with deionized water, remove water-soluble impurities, and then dry it in an 80℃ oven for 24h. Take it out and place it in a 500℃ muffle furnace for calcination for 2h to obtain activated illite powder. Add the activated illite powder to 10L of 4mol / L sodium hydroxide solution, stir it thoroughly and mix it evenly, seal it and heat it to 120℃ for hydrothermal reaction for 10h. After returning to room temperature, filter it, collect the filtrate and adjust its pH with 1mol / L hydrochloric acid solution To 6, add glass fiber felt and immerse it for 60 minutes, take it out and let it stand until no slurry drips to obtain wet fiber felt, then immerse the wet fiber felt in an appropriate amount of 1-butyl-3-methylimidazolium tetrafluoroborate and heat it to 70°C, keep it warm and age for 2 hours, then take it out and let it stand until no liquid drips, then place it in deionized water for replacement for 2 days, and then place it in ethanol and n-hexane respectively for replacement for 1 day, and replace fresh solvent every 12 hours during replacement. Finally, dry it in a 50°C oven for 24 hours.
[0038] The fire resistance performance of the ultra-high temperature resistant elastic wall flat cable prepared in this embodiment was tested with reference to Appendix D fire resistance test in the British fire-resistant cable standard BS6387. The test flame temperature was 2000±50°C and the continuous normal power-on time was ≥120min.
[0039] Example 3:
[0040] The process is basically the same as Example 1, except that the aging temperature is lowered to 60°C.
[0041] The preparation method of illite-based aerogel felt 1004 is as follows:
[0042] Take 1000g of illite, crush it through an 80-mesh sieve, wash it thoroughly with deionized water, remove water-soluble impurities, and then dry it in an 80℃ oven for 24h. Take it out and place it in a 500℃ muffle furnace for calcination for 2h to obtain activated illite powder. Add the activated illite powder to 10L of 4mol / L sodium hydroxide solution, stir it thoroughly and mix it evenly, seal it and heat it to 120℃ for hydrothermal reaction for 10h. After returning to room temperature, filter it, collect the filtrate and adjust its pH with 1mol / L hydrochloric acid solution To 6, add glass fiber felt and immerse it for 60 minutes, take it out and let it stand until no slurry drips to obtain wet fiber felt, then immerse the wet fiber felt in an appropriate amount of 1-butyl-3-methylimidazolium hexafluorophosphate and heat it to 60°C. After heat aging for 2 hours, take it out and let it stand until no liquid drips, then place it in deionized water for replacement for 2 days, and then place it in ethanol and n-hexane respectively for replacement for 1 day. During the replacement, replace the fresh solvent every 12 hours, and finally dry it in a 50°C oven for 24 hours.
[0043] The fire resistance performance of the ultra-high temperature resistant elastic wall flat cable prepared in this embodiment was tested with reference to Appendix D fire resistance test in the British fire-resistant cable standard BS6387. The test flame temperature was 2000±50°C and the continuous normal power-on time was ≥120min.
[0044] Example 4:
[0045] The process is basically the same as Example 1, except that the aging temperature is increased to 80°C.
[0046] The preparation method of illite-based aerogel felt 1004 is as follows:
[0047] Take 1000g of illite, crush it through an 80-mesh sieve, wash it thoroughly with deionized water, remove water-soluble impurities, and then dry it in an 80℃ oven for 24h. Take it out and place it in a 500℃ muffle furnace for calcination for 2h to obtain activated illite powder. Add the activated illite powder to 10L of 4mol / L sodium hydroxide solution, stir it thoroughly and mix it evenly, seal it and heat it to 120℃ for hydrothermal reaction for 10h. After returning to room temperature, filter it, collect the filtrate and adjust its pH with 1mol / L hydrochloric acid solution To 6, add glass fiber felt and immerse it for 60 minutes, take it out and let it stand until no slurry drips to obtain wet fiber felt, then immerse the wet fiber felt in an appropriate amount of 1-butyl-3-methylimidazolium hexafluorophosphate and heat it to 80°C. After heat aging for 2 hours, take it out and let it stand until no liquid drips, then place it in deionized water for replacement for 2 days, and then place it in ethanol and n-hexane respectively for replacement for 1 day. During the replacement, replace the fresh solvent every 12 hours, and finally dry it in a 50°C oven for 24 hours.
[0048] The fire resistance performance of the ultra-high temperature resistant elastic wall flat cable prepared in this embodiment was tested with reference to Appendix D fire resistance test in the British fire-resistant cable standard BS6387. The test flame temperature was 2000±50°C and the continuous normal power-on time was ≥120min.
[0049] Example 5:
[0050] The process is basically the same as Example 1, except that the aging temperature is increased to 90°C.
[0051] The preparation method of illite-based aerogel felt 1004 is as follows:
[0052] Take 1000g of illite, crush it through an 80-mesh sieve, wash it thoroughly with deionized water, remove water-soluble impurities, and then dry it in an 80℃ oven for 24h. Take it out and place it in a 500℃ muffle furnace for calcination for 2h to obtain activated illite powder. Add the activated illite powder to 10L of 4mol / L sodium hydroxide solution, stir it thoroughly and mix it evenly, seal it and heat it to 120℃ for hydrothermal reaction for 10h. After returning to room temperature, filter it, collect the filtrate and adjust its pH with 1mol / L hydrochloric acid solution To 6, add glass fiber felt and immerse it for 60 minutes, take it out and let it stand until no slurry drips to obtain wet fiber felt, then immerse the wet fiber felt in an appropriate amount of 1-butyl-3-methylimidazolium hexafluorophosphate and heat it to 90°C. After heat aging for 2 hours, take it out and let it stand until no liquid drips, then place it in deionized water for replacement for 2 days, and then place it in ethanol and n-hexane respectively for replacement for 1 day. During the replacement, replace the fresh solvent every 12 hours, and finally dry it in a 50°C oven for 24 hours.
[0053] The fire resistance performance of the ultra-high temperature resistant elastic wall flat cable prepared in this embodiment was tested with reference to Appendix D fire resistance test in the British fire-resistant cable standard BS6387. The test flame temperature was 2000±50°C and the continuous normal power-on time was ≥120min.
[0054] Comparative Example:
[0055] The method is basically the same as Example 1, except that the wet fiber felt is not added into 1-butyl-3-methylimidazolium hexafluorophosphate, but is directly placed in an oven at 70° C. for aging.
[0056] With reference to the fire resistance test in Appendix D of the British fire-resistant cable standard BS6387, the fire resistance of the ultra-high temperature resistant elastic wall flat cable prepared in this comparative example was tested. The test flame temperature was 2000±50°C and the continuous normal power-on time was 86 minutes.
[0057] Performance testing:
[0058] The illite-based aerogel felts prepared in Examples 1-5 and the comparative example were used as test samples;
[0059] The thermal conductivity of the sample was tested using a TC3200 thermal conductivity meter. The sample was placed in a room temperature chamber during the test. The unit is W / (m·K).
[0060] The pore volume of the sample was tested using the ASAP2460 fully automatic specific surface area and pore size tester. The sample was placed in a room temperature during the test. The unit is ml / g.
[0061] The test results are shown in Table 1 below:
[0062] ;
[0063] As can be seen from Table 1 above, the illite-based aerogel felt prepared in the present invention has an extremely low thermal conductivity;
[0064] From the comparison between Example 1 and Example 2, it can be seen that different ionic liquids have different effects on the thermal insulation performance of illite-based aerogel felt;
[0065] From the comparison between Example 1 and Examples 3-5, it can be seen that different aging temperatures have different effects on the thermal insulation performance of illite-based aerogel felt. When the aging temperature is 70°C, the thermal insulation performance of illite-based aerogel felt is optimal.
[0066] From the comparison between Example 1 and the comparative example, it can be seen that the ionic liquid, as a medium solvent during aging, has a positive effect on the microstructure and thermal insulation performance of the illite-based aerogel felt.
[0067] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. An ultra-high temperature resistant elastic wall flat cable, characterized in that: It has a flat structure, woven with cable core as braiding yarn and inorganic fiber as axis yarn; The cable core includes, from inside to outside, a conductor, a polyimide film insulation layer, a first mica tape wrapping layer, an illite-based aerogel felt, a second mica tape wrapping layer and an aramid fiber sleeve; The ultra-high temperature resistant elastic wall flat cable can be normally powered on for more than 120 minutes at a flame temperature of 1950-2050°C; The preparation method of the illite-based aerogel felt is as follows: After the illite is crushed, it is fully washed with deionized water and then dried. After being calcined, it is added to a sodium hydroxide solution. After a sealed hydrothermal reaction at 120°C for 10 hours, the precipitate is filtered out, the filtrate is collected and its pH is adjusted to 6, and the fiber felt is added thereto and fully soaked to obtain a wet fiber felt. The wet fiber felt is then aged, the solvent is replaced, and then dried.
2. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: The calcination temperature is 400-600°C and the calcination time is 1-5h.
3. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 2-6 mol / L.
4. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: The aging temperature is ≥60℃ and the aging time is 1-5h.
5. The ultra-high temperature resistant elastic-wall flat cable according to claim 4, characterized in that: Aging was carried out in ionic liquid.
6. The ultra-high temperature resistant elastic-wall flat cable according to claim 5, characterized in that: The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate and / or 1-butyl-3-methylimidazolium tetrafluoroborate.
7. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: During solvent replacement, the solvent was replaced in deionized water, ethanol and n-hexane for 1-3 days respectively.
8. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: Drying temperature ≤50℃.
9. The ultra-high temperature resistant elastic-wall flat cable according to claim 1, characterized in that: The inorganic fibers are quartz fibers and / or glass fibers.
Citation Information
Patent Citations
Composition for clay-aerogel composite, clay-aerogel composite, and method of making the same
US20120231251A1
Flat elevator cable and manufacturing method thereof
WO2017028376A1